Graphene‒Regulated Cardiomyogenic Differentiation Process of Mesenchymal Stem Cells by Enhancing the Expression of Extracellular Matrix Proteins and Cell Signaling Molecules. Issue 2 (15th August 2013) - Park, Jooyeon; Park, Subeom; Ryu, Seungmi; Bhang, Suk Ho; Kim, Jangho; Yoon, Jeong‐Kee; Park, Yoon Hwan; Cho, Sung‐Pyo; Lee, Seahyoung; Hong, Byung Hee; Kim, Byung‐Soo
<x xml:space="preserve">Abstract</x> The potential of graphene as a mesenchymal stem cell (MSC) culture substrate to promote cardiomyogenic differentiation is demonstrated. Graphene exhibits no sign of cytotoxicity for stem cell culture. MSCs are committed toward cardiomyogenic lineage by simply culturing them on graphene. This may be attributed, at least partially, to the regulation of expression levels of extracellular matrix and signaling molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>